Teaching Vocabulary by Using English Kid's Songs for the 3rd Grade Students of Linguistic Class Program (LCP) at MI Muhammadiyah 1 Pare – Kediri - Cayati NA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2019)
Abstract English cannot be separated from vocabulary learning, because it is a very important aspect in language skills in addition to aspects of speaking, listening and writing. In this case, the vocabulary is not only used for communication it can also improve English skills such as writing, speaking and listening skills. Lacking vocabulary is the reason why English is difficult to master. The students have been studying English for long time with the several methods, but they do not have an adequate vocabulary in English. Descriptive qualitative method is used by the researcher as research design. This research is intended to find out the descriptive outcome of the collected data and the interpretation of which as the conclusion to know how the curriculum, syllabus and implementation of teaching. The response of students toward the teaching of vocabulary process was consist of three terms, they are students’ difficulties, students’ perception on teaching learning process, and the advantages which can be taken by following this class. The first was about students’ difficulties, students had the problem in pronouncing and memorizing the vocabulary. The second was about their perception in teaching learning process. Generally the students enjoy this program because the teacher always asks the students to sing a song together. The students really like learning while singing a song. Even though they had some problems in the class; they liked this program because it gave them advantage to prepare themselves to build their vocabulary. By following this program, it increased their knowledge about vocabulary. Key word: Teaching Vocabulary, English Kid’s Song.